2011
DOI: 10.1039/c0cc03816d
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of carbohydrate microarrays through boronate formation

Abstract: A straightforward method for fabricating a stable and covalent carbohydrate microarray based on boronate formation between the hydroxyl groups of carbohydrate and boronic acid (BA) on the glass surface was used to identify carbohydrate-protein interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…[7][8][9] Lai et al have recently reported glyco-nanoparticles designed by fixing galactosyl ligands on metal nanoparticles and the unique affinity for asialoglycoprotein receptors in response to linker lengths and branch structures, plausibly affecting the surface density of the fixed galactose. 10 Other efforts also have been devoted to controlling the sugar density by organic synthesis routes; 11,12 however there have been few reports that the actual density of fixed carbohydrates is precisely determined by analytical characterization. Thus, a novel strategy and technique have been awaited for fabricating glyco-decorated biointerfaces with regulated surface sugar density, which is allowed to be defined in detail by instrumental analyses.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Lai et al have recently reported glyco-nanoparticles designed by fixing galactosyl ligands on metal nanoparticles and the unique affinity for asialoglycoprotein receptors in response to linker lengths and branch structures, plausibly affecting the surface density of the fixed galactose. 10 Other efforts also have been devoted to controlling the sugar density by organic synthesis routes; 11,12 however there have been few reports that the actual density of fixed carbohydrates is precisely determined by analytical characterization. Thus, a novel strategy and technique have been awaited for fabricating glyco-decorated biointerfaces with regulated surface sugar density, which is allowed to be defined in detail by instrumental analyses.…”
Section: Introductionmentioning
confidence: 99%
“…6d). 70 In this process, unmodified glycans are attached to the boronic acid-functionalized surface through complexation of the boronic acid with 1,2-or 1,3-diols of carbohydrates. Although the above approach has the advantage of easy construction of glycan microarrays, its major drawback is the sitenonspecific attachment of glycans to the surface.…”
Section: Immobilization Methodsmentioning
confidence: 99%
“…Boronic acids (BAs) can form covalent bonds with 1–2 and 1–3 cis ‐diol groups to generate stable cyclic esters (Fig. A) . Boronate esters are selectively formed at high pH values, and the reaction is reversible under acidic conditions.…”
Section: Methods Based On Boronate Affinitymentioning
confidence: 99%